IMPROVING THE QUALITY OF TRANSPORT SERVICES THROUGH THE DEVELOPMENT OF LOGISTICS INFRASTRUCTURE - Soyibovich, Murodov Abdurahim; Saparbaevna, Atadjanova Zulfiya (The journal of contemporary issues in business and government, 2021)
Determining the capacity of a logistics infrastructure as a whole is more complicated because it consists of several elements. Logistics infrastructure is a large integrated system consisting of a set of regulatory, transport, storage and processing, service, financial, information and scientific elements, the potential of which varies over time. The results of the assessment will form the basis for the development of the Concept of Logistics Infrastructure Development Strategy.